2022
DOI: 10.7759/cureus.32708
|View full text |Cite
|
Sign up to set email alerts
|

Physician Knowledge and Attitudes Toward the Adoption of Peritoneal Dialysis in the Treatment of Patients With End-Stage Kidney Disease

Abstract: IntroductionHemodialysis (HD) is a significant contributor to Medicare spending. Peritoneal dialysis (PD) is a lower-cost dialysis modality with non-inferior clinical outcomes. Recent initiatives at the federal level have emphasized shifting dialysis from in-center to home modalities, namely, PD. Such policy has been slow to impact the distribution of HD and PD due to multiple barriers, including at the provider level. Previous research has characterized the role of patient knowledge gaps and preferences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study from US demonstrated the impact of physician knowledge and attitudes toward PD in the under-utilization of PD as a dialysis modality; the need for increased provider education around PD candidacy and the benefits of shifting dialysis care to the home. Even in developed countries, physician knowledge and attitudes toward PD had huge impact and lead to under-utilization of PD as a dialysis modality (Lalani et al, 2022). In this study, the knowledge of physicians on CAPD was very good; their attitudes were positive.…”
Section: Figure (5) the Frequency Distribution Of The Source Of Infor...mentioning
confidence: 65%
See 3 more Smart Citations
“…The study from US demonstrated the impact of physician knowledge and attitudes toward PD in the under-utilization of PD as a dialysis modality; the need for increased provider education around PD candidacy and the benefits of shifting dialysis care to the home. Even in developed countries, physician knowledge and attitudes toward PD had huge impact and lead to under-utilization of PD as a dialysis modality (Lalani et al, 2022). In this study, the knowledge of physicians on CAPD was very good; their attitudes were positive.…”
Section: Figure (5) the Frequency Distribution Of The Source Of Infor...mentioning
confidence: 65%
“…Third portion was knowledge on possible obstacles on CAPD; PD solutions, skin infection, morbid obesity, PD catheter related problems, caregiver expertise, cost, diabetes mellitus, peritonitis, electricity and sustainability. As demonstrated in figure (2), their view on likely obstacles to CAPD were as follows: PD solutions (71%); skin infection (68%); morbid obesity (53.8%); PD catheter related problems (42%).…”
Section: Figure (1) Response Of Physicians' Agreement Percentage On C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these successes in improving catheter outcomes and reducing technique failure, the utilisation of PD in Japan has remained flat over the past decade, 1,27,28 implicating the influence of other globally recognised government, physician and patient barriers that must be addressed to effectively grow PD. [29][30][31] On a final note, throughout the manuscript, Sakurada and company used mixed terminologies of catheter patency failure and survival and technique failure and survival, but they were clear in how the terms were applied. However, it has been suggested by the SONG-PD (Standardized Outcomes in Nephrology-Peritoneal Dialysis) consensus workshop to use positively framed terminology, therefore, survival instead of failure, in reporting patient outcomes to convey a more appropriate perception of PD therapy.…”
mentioning
confidence: 99%